(untitled) (Vietnam Journal of Agriculture and Environment, 2023)
The article presents the results of the current status of Snout Otter Clam farming techniques in Quang Ninh, Hai Phong, and Khanh Hoa through questionnaires and information collection in order to determine the main technical parameters in the current Snout Otter Clam culture and some technical solutions that need to be implemented. This is the first facility to serve the construction of a highly efficient and sustainable commercial Snout Otter Clam farming technology process. Regarding the current status of farming techniques, the total area of Snout Otter Clam farming in the three surveyed provinces is estimated at 299 hectares, and farmers mainly apply the cage culture placed in the tidal flat on about 214 hectares. The stocking size is from 1-3cm/individual with a density of 25-55 fish/cage, and the time of stocking is from March to April every year. The culture period is 10-14 months per crop, the harvested Snout Otter Clam size is 25-60 g/individual, the survival rate is 25-60%, and the yield is 355.37-470.84 g/cage/crop. Regarding the epidemic situation, there was no outbreak of disease. However, it was still recorded that diseased Snout Otter Clam appeared sporadically during the culture period. The characteristic presentation described is similar to that of Virus-like particles (VLPs). Snout Otter Clam are diseased at seed stage (size from 2-3cm) and commercial stage (size from 20-35g/head). The research results have provided the current status of Snout Otter Clam farming and suggested the main solutions that need to be taken to develop an effective and sustainable Snout Otter Clamculture.